Iqbal : poet-philosopher of universal values - Dil, Anwar S.; Intercultural Forum (San Diego, Calif.) (Islamabad : Dost Publications ; San Diego : Intercultural Forum, 2013)
History and criticism on the work of Sir Muhammad Iqbal, 1877-1938.
Includes bibliographical references (pages 319-326) and index.
Keywords: Iqbal, Muhammad, -- Sir, -- 1877-1938 -- Criticism and interpretation